A medicalização na Educação e a formação inicial do pedagogo - Calado, Vânia Aparecida (2019)
This research aimed to develop and analyze pedagogical mediations in the learning process of the concept of medicalization in education with Pedagogy students. For this, based on the theoretical framework of Historical-Cultural Psychology, a formative experiment was conducted following Davydov's proposition, between August and December 2016, with a group of 25 night-shift sixth period students, presently attending a public university of Natal, RN. The experiment was developed in 16 weekly classes, distributed in three stages, preceded by the survey about the knowledge held about medicalization. The planning of the pedagogical mediations was based on the conceptual hierarchy designed to approach the scientific concept of medicalization in education. In the first stage, activities were developed to work on the social function concepts of the school and the pedagogue and the relationship between society and school. In the second stage, the concept of play was initially worked to rescue childhood memories and the playful experience of students, and, later, in the elaboration of intervention proposals in playfulness based schools where they were interning. In the third stage, the concepts of health, disease, society standardization, biological determinism, medicalization of life and data on drug consumption were approached. The analysis of the written records of seven selected students indicated that they understood that the society based on capitalism mechanizes, normalizes and dehumanizes the subjects, reaches the pedagogues and leads them to elaborate disciplinary pedagogical practices that do not develop learning and creativity, consequentially, students who fail at school are assigned illnesses to be treated by medication with the influence of the pharmaceutical industry. It is concluded that the formative experiment enabled mediations that promoted psychic changes, qualified thought processes for conceptual learning about medicalization in education and contributed to identify possibilities of coping with the phenomenon, which playfulness was pointed as an option.